Exacerbation of diabetes due to F. Nucleatum LPS-induced SGLT2 overexpression in the renal proximal tubular epithelial cells - Aiko Seki; Koichiro Kajiwara; Jumpei Teramachi; Masahiko Egusa; Takuya Miyawaki; Yoshihiko Sawa (BMC Nephrology)
Abstract Background Diabetes treatments by the control of sodium-glucose cotransporter 2 (SGLT2) is commonly conducted while there are still uncertainties about the mechanisms for the SGLT2 overexpression in kidneys with diabetes. Previously, we have reported that glomeruli and proximal tubules with diabetic nephropathy express toll-like receptor TLR2/4, and that the TLR ligand lipopolysaccharide (LPS) of periodontal pathogens have caused nephropathy in diabetic model mice. Recently, many researchers suggested that the periodontal pathogenic bacteria Fusobacterium (F.) nucleatum has the TLR4-associated strong activator of the colorectal inflammation and cancer. The present study aimed to investigate the possibility of F. nucleatum as an exacerbation factor of diabetes through the renal SGLT2 induction. Methods The induction of the SGLT2 by F. nucleatum LPS (Fn-LPS) were investigated in the streptozotocin-induced diabetic mouse renal tissue and cultured renal proximal epithelial cells. The changes of blood glucose levels and survival curves in diabetic mice with Fn-LPS were analyzed. The Fn-LPS-induced SGLT2 production in the diabetic mouse renal tissue and in the cultured proximal epithelial cells was examined by ELISA, quantitative RT-PCR, and immunohistochemical analysis. Results The SGLT2 expression in the cultured mouse tubular epithelial cells was significantly increased by TNF- or co-culture with Fn-LPS-supplemented J774.1 cells. The period to reach diabetic condition was significantly shorter in Fn-LPS-administered diabetic mice than in diabetic mice. All Fn-LPS-administered-diabetic mice reached humane endpoints during the healthy period of all of the mice administered Fn-LPS only. The promotion of the SGLT2 expression at the inner lumen of proximal tubules were stronger in the Fn-LPS-administered-diabetic mice than in diabetic mice. The renal tissue SGLT2 mRNA amounts and the number of renal proximal tubules with overexpressed SGLT2 in the lumen were more in the Fn-LPS-administered-diabetic mice than in diabetic mice. Conclusions This study suggests that F. nucleatum causes the promotion of diabetes through the overexpression of SGLT2 in proximal tubules under the diabetic condition. Periodontitis with F. nucleatum may be a diabetic exacerbating factor.